2020
DOI: 10.1002/stem.3253
|View full text |Cite
|
Sign up to set email alerts
|

The Sca-1+ and Sca-1− mouse prostatic luminal cell lineages are independently sustained

Abstract: The phenotypic and functional heterogeneity of the mouse prostate epithelial cell lineages remains incompletely characterized. We show that the Sca‐1+ luminal cells at the mouse proximal prostate express Sox2. These cells are replicative quiescent, castration resistant, and do not possess secretory function. We use the Probasin‐CreERT2 and Sox2‐CreERT2 models in concert with a fluorescent reporter line to label the Sca‐1− and Sca‐1+ luminal cells, respectively. By a lineage tracing approach, we show that the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 52 publications
(80 reference statements)
2
24
0
Order By: Relevance
“…Previously, we discovered a distinct Sca-1 + Nkx3.1 − luminal cell population that resides in the mouse proximal prostatic duct adjacent to the urethra ( 16 , 17 ). These cells express Sox2, are replicative quiescent, and possess a facultative bipotent differentiation capacity ( 16 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we discovered a distinct Sca-1 + Nkx3.1 − luminal cell population that resides in the mouse proximal prostatic duct adjacent to the urethra ( 16 , 17 ). These cells express Sox2, are replicative quiescent, and possess a facultative bipotent differentiation capacity ( 16 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Sca-1 + luminal cells do not rely on androgen for their survival ( 17 , 18 , 20 ). To examine whether tumors derived from the Sca-1 + luminal cells inherit the castration resistant property of their cells of origin, we castrated K8-Pten mice at 3 months after tamoxifen induction ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…The human TACSTD2 high luminal cells share molecular features with the castration resistant Sca-1 + luminal cells in mice ( 28 ). To determine the androgen dependency of the tumor organoids, we passaged and cultured organoid cells without testosterone but with enzalutamide.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, we set out to assess whether mouse prostate organoids are a representative and informative model for the study of the prostate epithelium, in light of recent discoveries on prostate cellular heterogeneity and dynamics 27,28,[30][31][32]34,38 . Considering our interest in signalling, we focused on a culture method in defined media conditions.…”
Section: Mouse Prostate Organoid Cultures Enable the Continuous Expanmentioning
confidence: 99%
“…Recent single-cell studies have confirmed the enrichment of a variety of epithelial progenitors -basal, luminal proximal (LumP), and periurethral (PrU) cells -in this anatomical district, though also present at low frequency in the distal compartment [27][28][29][30][31][32] . Such cells are known to be particularly quiescent during homeostasis 33,34 , but also to exhibit extensive regenerative potential in ex-vivo assays 31,35 .…”
Section: Introductionmentioning
confidence: 99%